Constructing ‘the parents’ in primary schools in Greece: special education teachers’ whispers - Boutskou, Evangelia (International Journal about Parents in Education, 2023)
The Greek educational system is highly centralized and the communication between parents and teachers is considered as a marginal or a grey area in the school function. Educational legislation favours parents’ involvement rather than participation and implies an imbalance between parents and professionals. Drawing on a study using a life history approach, this paper considers the ways in which special education teachers in both special education schools and integration units perceive the parents of their students. The boundaries between expert knowledge and personal experience form a contested terrain of power relationships. These relationships are shaped by circumstances and are highly contextualized. Special school teachers deem parents in a deficit discourse while Integration unit teachers deem parents in a client discourse. The construction of the “parents” seems to be a gendered and social class issue as well. This work also reveals some implications for the teachers’ training programmes in order to ensure a more equal partnership at more inclusive and democratic schools.